Social panorama of Latin America. (United Nations ECLAC, 2005)
The 2004 edition of the Social Panorama of Latin America analyses the major demographic changes that have occurred in the region over the past few decades, examines the socioeconomic status of Latin American youth, looks at institutional and programmatic guidelines for youth policies and describes how household structures and family roles have changed. As in past years, recent trends in poverty and income distribution in the Latin American countries are also reviewed. The first chapter presents projections of poverty and indigence rates for 2003 and 2004. The conclusion drawn from these projections is that the region has failed to gain any ground since 1997 in its effort to combat poverty and actually witnessed a slight deterioration in this respect in 2003. Nevertheless, stronger growth projections for 2004 indicate that many countries are still in a position to succeed in halving extreme poverty by 2015. Meanwhile, Latin America continues to be the world region with the worst income distribution indicators of all. This situation has been exacerbated by the fact that some countries have actually witnessed an increase in income concentration. This heightens the urgency of developing distributive policies to increase low-income stratas incomegenerating capacity with the help of stronger social safety nets and a more inclusive production model. The chapter on major demographic changes in Latin America and the Caribbean draws heavily upon work done by the Latin American and Caribbean Demographic Centre (CELADE) - Population Division of ECLAC in connection, in particular, with the agreements reached at the International Conference on Population and Development (Cairo, 1994).